PENDEKATAN MERDEKA BELAJAR PADA PEMBELAJARAN KONTEKSTUAL DALAM MENINGKATKAN KUALITAS PENDIDIKAN USIA DINI - siska meilina (Program Studi Pendidikan Islam Anak Usia Dini, 2024)
In Indonesia there is still a great need to improve education. This is a problem because the teacher-centered education system makes children less independent and creative. In addition, teachers apply theory in learning without tools, making children not understand what has been taught. The author uses the literature research method and collects information in books, articles or journals, internet sources and from other relevant sources. The results of the literature review discuss how contextual learning, also known as self-directed learning, is a type of learning that combines theory with real-world circumstances. It makes learning more concrete and meaningful, and gives children the freedom to seek and solve problems in group and individual learning, which helps them become more creative and independent